THE INFLUENCE OF LEADERSHIP, COMPENSATION AND CAREER DEVELOPMENT ON EMPLOYEE ENGAGEMENT AT PT. BANK ACEH SYARIAH MEDAN REGION - Emi Wakhyuni; Asmuni Asmuni; Rizal Agus (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to analyze the effect of leadership, compensation and career development on employee engagement. This study uses quantitative methods involving 78 respondents, namely all employees of PT. Bank Aceh Syariah Medan Region. Data was collected using the distribution of questionnaires and interviews, secondary data was collected : agencies and literature studies. Data obtained were analyzed using statistical formulas, namely by using the validity test, reliability test and multiple linear regression analysis with the SPSS version 23.0 program. results are study indicate that leadership has positive , significant effect on employee engagement with a sig. 0.000 0.05. Furthermore, compensation has a positive and significant effect on employee engagement with values and sig. 0.013 0.05. Meanwhile, career development does not have a significant effect on employee engagement with a sig value. 0.205 0.05. Leadership, compensation and career development simultaneously affect employee engagement with a value of sig 0.000 0.05. Based on the adjusted R Square value of 0.775 which can be called the coefficient of determination which in this case means 77.5% employee engagement can be obtained and explained by leadership, compensation and career development. While the remaining 22.5% is explained by other factors or variables outside. From the results of researh, it can be concluded that Bank Aceh Syariah Medan Region needs to evaluate the attitude of the leadership towards their subordinates and provide appropriate compensation to employees as motivation in strengthening employee engagement.Keywords: Leadership; compensation; Career Development; Employee Engagement.